Analisis Pengaruh Perubahan Tekanan Vakum Kondensor Terhadap Heat Rate Turbin Di PLTU Moramo Sebelum dan Sesudah Perawatan - Saputro, Bagus Andi; Sudia, Budiman; Kadir, Abd. (Teknik Mesin Universitas Halu Oleo, 2021)
PLTU Moramo is one of the Independent Power Producers (IPP) that supplies electricity to PT PLN. PLTU Moramo make use of turbine-generator with an installed capacity of 2x50 MW Steam Turbine - Full Condensing. PLTU Moramo Unit 1 experienced an increase in the condenser vacuum value after routine maintenance, the increase in the vacuum value affected to the heat rate and efficiency of the steam turbine cycle. The research conducted is to analyzes the effect of changes in the value of the condenser vacuum on the heat rate and efficiency of the steam turbine cycle by using a thermodynamic analysis approach and energy input-output methods. Data analysis uses actual parameters taken from the Distributed Control System (DCS) during normal operation. The results obtained in this study indicate that an increase in the condenser vacuum value affects the heat rate and efficiency of the steam turbine cycle, an increase in the vacuum value of -1 kPa results in a decrease in the average turbine heat rate of 57,673 kJ/kWh for a load of 40 MW Net and 93,575 kJ/ kWh for 50 MW Net load. Meanwhile, the average value of the steam turbine cycle efficiency increased by 0.37% for a load of 40 MW Net and 2.19% for 50 MW Net. Keywords: heat rate, efficiency, PLTU, vacuum